Uniqueness seeking and demand estimation in the German automobile industry - Marco Guerzoni; René Soellner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper empirically analyzes the determinants of demand in the German automobile industry. Our primary goal is to refine the existing literature on that topic by exploring the impact of uniqueness seeking behaviour of individuals on the demand schedule. Using a dataset on the segment of compact cars in the German market, we show that consumers have an intrinsic need for uniqueness seeking, and the degree a product satisfies this need is to be considered as an additional product characteristic.
Keywords: D12; L11; L15; L62; 330; DEMAND ESTIMATION; DISCRETE CHOICE; DIFFERENTIATED PRODUCTS; Kraftfahrzeug; Nachfrage; Konsumentenverhalten; Produktdifferenzierung; Kraftfahrzeugmarkt; Schätzung; Deutschland